A Systematic Review of Reproductive Counseling in Cases of Parental Constitutional Reciprocal Translocation (9;22) Mimicking BCR-ABL1 - Gao, Zimeng; Rice, Stephanie M.; Wodoslawsky, Sascha; Long, Sara C.; Wang, Zi-Xuan; Torkzaban, Mehnoosh; Angarita Africano, Ana Milena; Liu, Jinglan; Al-Kouatly, Huda B. (Frontiers in Genetics, 2022)
We aim to determine the spectrum of cytogenetic abnormalities and outcomes in unbalanced offspring of asymptomatic constitutional balanced t(9;22) carriers through a systematic literature review. We also include a case of a constitutional balanced t(9;22) carrier from our institution. Among the 16 balanced t(9;22) carriers in our review, 13 were maternal and 3 were paternal. Of the 15 unbalanced translocation cases identified, 13 were live births, one was a missed abortion, and one resulted in pregnancy termination. The spectrum of established syndromes reported among the live births was the following: trisomy 9p syndrome (6/13), dual trisomy 9p and DiGeorge syndrome (3/13), dual 9q subtelomere deletion syndrome and DiGeorge syndrome (1/13), 9q subtelomere deletion syndrome (1/13), DiGeorge syndrome (1/13). One unbalanced case did not have a reported syndrome. The phenotype of the unbalanced cases included cardiac abnormalities (5/13), neurological findings (7/13), intellectual disability (6/10), urogenital anomalies (3/13), respiratory or immune dysfunction (3/13), and facial or skeletal dysmorphias (13/13). Any constitutional balanced reciprocal t(9;22) carrier should be counseled regarding the increased risk of having a child with an unbalanced translocation, the spectrum of possible cytogenetic abnormalities, and predicted clinical phenotype for the unbalanced derivative.